1985-1991-ЖЫЛЛАРДА ҚАРАҚАЛПАҚСТАН ПОЛИГРАФИЯ ӨНДИРИСИ: МАШҚАЛАЛАР ҲӘМ ШЕШИМЛЕР - Идрисов, Р. (FAN va JAMIYAT, 2024)
This article is devoted to the crisis of the publishing industry in Karakalpakstan and the collapse of the ideological foundations of the Soviet state, the history of growing problems in the publishing industry and the search for their solutions. The chronological scope of the article includes the period from the second half of 1985 to the beginning of 1991.